DOES LOCATION AFFECTS IN DIFFERENTIATING A UNIVERSITY? - Meenu Bhardwaj, R.S. Bawa, Sanjeet Singh (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The savagely aggressive HE advertise has driven HEIs to put critical assets in building an unmistakable personality. A HEI’s area frames a natural piece of its own personality and uniqueness of area offers a chance to separate. Anyway there has been constrained examination of how area is utilized by HEIs and a little thought of how area can give a compelling methods for separation. Through the viewpoint of place marketing, knowledge is shared through this exploratory paper into the way HEIs depict area and talks about whether area can offer a wellspring of separation. The current paper is a systematic review using PRISMA guidelines. Total 573 papers have been downloaded from the Scopus and after evaluating them as per PRISMA guidelines 113 papers have been selected and evaluated.